K izbranim problemom narodnega preroda - Zelenka, Miloš (Slavistična revija, 2014)
The article deals with the definition and periodization of the national revival as a complex process of forming a modern national society. It also aims to discern connections between the periodization from the points of view of history on the one hand and literary criticism on the other. The former involves phases of scholarly inquiry, national activism, and populism, while the latter divides the Czech National Revival into periods according to literary movements. The article calls for interdisciplinary and comparative literary history that would be in agreement with the "ingressive" concept of literary history. Its goal would be to provide an accurate representation of the Central European National Revival as a whole, punctuated by numerous interruptions, digressions, breaks, and lacunae.
Keywords: Central Europe; Czech literature; Czech national revival; Czech Republic; Češka; češka književnost; history of literature; literarna zgodovina; literary history; narodni preporod; Realism; realizem; Romanticism; romantika; Srednja Evropa